Enhanced thermoelectric properties of In2O3(ZnO)5 intrinsic superlattice ceramics by optimizing the sintering process. Issue 79 (26th October 2017) - Cui, Li-Jun; Ge, Zhen-Hua; Qin, Peng; Feng, Jing
Abstract : Thermoelectric (TE) materials have a promising application as they can interconvert thermal energy to electrical energy directly. Abstract : Thermoelectric (TE) materials have a promising application as they can interconvert thermal energy to electrical energy directly. Oxide TE materials have attracted more attention for this application due to their high temperature stability. In this work, In2 O3 (ZnO)5 intrinsic superlattice ceramics with a layered structure were synthesized by reaction sintering a mixed powder of In2 O3 and ZnO at 1200 °C for different holding times ( t = 6, 8, 10, 12 and 15 h) in air. Their thermoelectric properties including the electrical conductivity, Seebeck coefficient and thermal conductivity, were measured from 323 to 973 K. The thermoelectric properties depended on the holding time. The highest ZT value of 0.19 at 973 K was obtained for the sample with a 12 h holding time.